2017
DOI: 10.1055/s-0043-116386
|View full text |Cite
|
Sign up to set email alerts
|

Initiation of Basal Insulin Analog Treatment for Type 2 Diabetes and Reasons Behind Patients’ Treatment Persistence Behavior: Real-World Data from Germany

Abstract: Quality interactions between physicians or other HCPs and their patients before and during the initiation of basal insulin may help to manage patient expectations and to improve persistence to insulin therapy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 25 publications
0
2
1
Order By: Relevance
“…Compared with previous studies, we found that much lower proportions of discontinuers reported hypoglycaemia (6.7%) or weight gain (2.4%) as the reasons for discontinuation. In this study, general hypoglycaemia happened in 9.7% and 7.7% of discontinuers and continuers in the past month (weight gain >2 kg: 16.0%, 12.1%), respectively, whereas the proportion of severe hypoglycaemia after BI initiation was very low (0.6%).…”
Section: Discussioncontrasting
confidence: 98%
“…Compared with previous studies, we found that much lower proportions of discontinuers reported hypoglycaemia (6.7%) or weight gain (2.4%) as the reasons for discontinuation. In this study, general hypoglycaemia happened in 9.7% and 7.7% of discontinuers and continuers in the past month (weight gain >2 kg: 16.0%, 12.1%), respectively, whereas the proportion of severe hypoglycaemia after BI initiation was very low (0.6%).…”
Section: Discussioncontrasting
confidence: 98%
“…Laferton et al (15) also showed an injectable medication was expected to be more effective than an oral one. Reduction of glucose to a target level was the number one most expected benefit, 7 out of 10 insulin participants anticipated this result, higher than 42 and 61% reported by multinational studies (20,21). In contrast, 5 out of 10 metformin users expected this benefit, a result lower than that documented in primary care of 70% (18).…”
Section: Type Of Medicationmentioning
confidence: 72%
“…One study found that only one-fifth of persons with diabetes expected to take glucose-lowering agents for the rest of their lives ( 19 ). Moennig et al ( 20 ) found that 42% of insulin users expected an improvement in glucose, and fulfillment of this expectation was the main cause of uninterrupted use. Naegeli et al ( 21 ) documented a higher percentage of insulin users anticipate achieving optimal glucose levels (61%).…”
Section: Introductionmentioning
confidence: 99%